Answer:
3 socks
Step-by-step explanation:
Given that, there are 10 red socks and 10 blue socks which are mixed up in the dresser drawer.
The socks are identical except the color.
We need to find out, the minimum number of socks to be taken out from the dark room so that there is at least a pair of matching socks comes out of the drawer.
Let us consider the cases:
First Two socks pulled out of the drawer.
Case 1: Both are red or both are blue.
In this case, the matching pair is ready.
But there can be other case as well.
Case 2:
One red and one blue color taken out.
Now, when we pull the third, there will be either red or blue.
That will make a pair.
Therefore, to cover up all the cases and to be certain to get a matching pair out of the drawer, at least 3 socks must be taken out.
So, the answer is:
We need to take out at least 3 socks.
The number of socks that determines a matching pair is an illustration of probabilities
The smallest number of socks is 3
The number of socks is given as:
[tex]\mathbf{Red = 10}[/tex]
[tex]\mathbf{Blue = 10}[/tex]
There are two colors of socks in the drawer
This is represented as:
[tex]\mathbf{n = 2}[/tex]
So, the smallest number of socks to determine matching pair is
[tex]\mathbf{Smallest = n + 1}[/tex]
Substitute 2 for n
[tex]\mathbf{Smallest = 2 + 1}[/tex]
Add
[tex]\mathbf{Smallest = 3}[/tex]
Hence, the smallest number of socks is 3
Read more about probabilities at:
https://brainly.com/question/10837034
Vera examined a random sample of deodorants distributed by her company. She found the following probabilities:
P (for men) = 0.55
P (botanic scent) = 0.18
P (for men and botanic) = 0.05
Find the probability that a deodorant is for men, given that it has a botanic scent.
Answer: 5/18
Step-by-step explanation:
a person can pay $21 for a membership to the history for just $1 per visit what is the maximum number of this has a number of the history be seen you can make of a total cost of $30
Answer:
Your question doesnt make sense
Step-by-step explanation:
A local parking garage charges $5 for the first hour and $1.25 for each additional hour. Write an equation in function notation form. Tell me how much it would cost if you left your car for a total of 6 hours.
What other information do you need to prove GHK ≅ KLG by SAS?
The image is a quadrilateral GHKL and a diagonal GK is drawn such that it forms two triangles GHK and KLG. Sides GL and KH are marked as congruent.
A. ∠KHG ≅ ∠GLK
B. ∠HGK ≅ ∠LKG
C. ∠GHK ≅ ∠KLG
D. ∠HKG ≅ ∠LGK
Answer: D. ∠HKG ≅ ∠LGK
Step-by-step explanation:
Given: Quadrilateral GHKL where diagonal GK is drawn such that it forms two triangles GHK and KLG.
Side GL ≅ Side KH
Now, GK is common in both triangles GHK and KLG.
and GK ≅GK
SAS congruence rule: If any two sides and the angle included between the sides of one triangle are congruent to the corresponding two sides and the angle between the sides of the second triangle, then the two triangles are said to be congruent.
So ∠HKG must be congruent to ∠LGK ( angles between the congruent sides).
Hence, the correct option is D. ∠HKG ≅ ∠LGK
Question:
What other information do you need to prove ∆ GHK ≅ ∆ KLG by SAS?
Answer:
HKG ≅ LGK
Find f (77)
f(p)=7/11p-10:
A: f(77)=59
B: f(77)=39
C: f(77)=49
D: f(77)=67
Answer:
I don't know, the way it is typed confuses me. Is it 7/11 TIMES p-10 or is p-10 with the 11 as the denominator? but I do hope this helps:
Step-by-step explanation:
So first I subtracted 7/11 from each side:
f(p)-7/11=(7/11-7/11)p-10
Now we are left with f(4/11p)=p-10
Now to get the variable "p" on one side, I subtracted 4/11p from both sides:
f(4/11p-4/11p)=(p-4/11p)-10
Now we are left with f=7/11p-10
Now we want the "p" to be 1p so we multiply each side by the reciprocal of 7/11:
f(11/7)=(7/11*11/7)p-10
Now we have 1 4/7f=p-10
Now we subtract 4/7 from each side and get:
f=p-9 3/7
And that's as far as I could simplify it, sorry if it's wrong... lol
The required value of f (77) is 39 for the given equation. The correct answer would be an option (B).
What is the equation?The equation is defined as mathematical statements that have a minimum of two terms containing variables or numbers that are equal.
The equation is given in the question, as follows:
f (p) = (7/11) p - 10
We have to determine the value of f (77) for the given equation.
As per the question, we have
f (p) = (7/11) p - 10
Substitute the value of p = 77 in the above equation,
f (77) = (7/11)(77) - 10
f (77) = 7 x 7 - 10
f (77) = 49 - 10
Apply the subtraction operation, and we get
f (77) = 39
Thus, the value of f (77) is 39.
Learn more about the equation here:
brainly.com/question/10413253
#SPJ2
Which point is on the graph of f(x) = 2 · 5*
O
A. (1,10)
O B. (10,1)
O
C. (0,0)
O D. (0,10)
Answer: The answer is (1,10)
Step-by-step explanation:
What is the sum of 5.8 + 8.09?
Answer:
13.80.........................
Answer:
the answer is 13.89
Step-by-step explanation:
pls pls help!! i will mark you as brilliant!!
Answer:
[tex]M-N=8x^2+11x-9\\[/tex]
Step-by-step explanation:
[tex]We\ are\ given\ that:\\M=5x^2+7x-4\\N=-3x^2-4x+5\\\\Hence,\\M-N=5x^2+7x-4-(-3x^2-4x+5)\\M-N=5x^2+7x-4+3x^2+4x-5\\M-N=5x^2+3x^2+7x+4x-4-5\\M-N=8x^2+11x-9\\[/tex]
Answer:
8x^2+11x^2-9
Step-by-step explanation:
5x^2-(-3x^2)=8x^2
7x-(-4x)=11x
-4-5=-9
1. Cindy did an experiment. She started out with 700 bacteria cells. She found that the growth rate of the
bacteria cells was 4.3%. Create an equation for the situation that would work for any time, x. Type your
equation into Desmos to make a graph that represents her experiment.
given and, write the new function rule (equation) for function and describe (using words) the two transformations that occur between function and function.
i already got the equation for the first part: y=700(1.043^x) but i don’t understand the second part.
Answer:
See the screenshot! :)
Step-by-step explanation:
we have a exponential function of the form
y=a([tex]b^x[/tex])
where
y ---> is the population of bacteria
x ---> the number of hours
a is the initial value or y-intercept
b is the base of the exponential function
r is the rate of change
b=(1+r)
we have
a=700 bacteria
r=5%=5/100=0.05
so
b=1+0.05=1.05
substitute
y=700([tex]1.05^x[/tex])
For x=20 hours
substitute in the equation and solve for y
y=700(1.05)^20= 1,857 bacteria
Hope this helped! :)
5. An object is accelerating at 10 m/s2. If the mass is doubled, what
happens to the celeration?
|
I
Answer:
20
If the net force on an object is doubled, its acceleration will double If the mass of an object is doubled, the acceleration will be halved.
please help and answer
Answer:
Equation is the second one, term is the first one, expression is the third one, inequality is the last one
Step-by-step explanation:
Answer: equation is the one with the =, expression is 4x+(-2), inequality is the one with the greater than sign, and the term is -9
A medication is administered with a dose of 10 milligrams. After 3 hours there are 6.5 milligrams in the patient's system. What is the half life of the medication, in hours? Round to one decimal place.
Answer:
4.8 hours
Step-by-step explanation:
The formula for half life is given as:
t½ = t × In(2)/In(No/Nt)
Where
t½ = Half life
t = time in hours = 4
No = Initial amount = 10mg
Nt = Final amount after 3 hours = 6.5 mg
t½ = 3 × In(2) /In(10/6.5)
t½ = 4.8271216522281 hours
Approximately = 4.8 hours
The half-life of the medication, in hours, is 4.8 hours.
Given that,
Medication is administered with a dose of 10 milligrams. After 3 hours there are 6.5 milligrams in the patient's system.Based on the above information, the calculation is as follows:
The following formula should be used:
[tex]= t \times ln(2)\div ln(No\div Nt)[/tex]
Here
t denotes the time in hours i.e. 4
No means the Initial amount i.e. 10mg
Nt means Final amount after 3 hours i.e. 6.5 mg
So,
[tex]= 3 \times ln(2) \div ln(10\div 6.5)[/tex]
= 4.82
= 4.8 hours
Therefore we can conclude that the half-life of the medication, in hours, is 4.8 hours.
Learn more: brainly.com/question/24169758
How many students participated in the survey
Answer:
more details are needed
Answer:
this questioned needs more details I don't understand
How do Find what I want to be when I'm older??? any suggestions for good money that doesn't have to do with doctors or lawyers
Step-by-step explanation:
You dont have to just wait.
Youll figure out what you like
Answer:
ask what would you like to do or do you make enough money simple questions
i dont know how to tell this kid i like him.... sounds like elemtray shi but i really have no clue how to ask him to hangout at my house and stuffff.... help plzzzz
Answer:
Just casually ask him to hang out love
Step-by-step explanation:
Answer:
i have a boyfriend, and he asked me, but my last relationship i basically asked, he was going to ask me but he got scared and said if i wanted to be his friend, and i said yeah of course, so after that he asked if i wanted to be besties cause he choked again so then i said what about girlfriend? and he said he'd think, we ended up getting together for a good month and a half, so i suggest just telling him, or give him a call and ask him if he wants to come over and do homework together or something.
Step-by-step explanation:
Write the equation of a line in slope intercept form giving the following:
A: m=2 (0,-7)
B: (3,-4) (-2,1)
C: f(2)=6 f(0)=5
Answer:
Equation of a straight line is given as y = mx+c
m = slope or gradient or dy/dx or y2 - y1/ x2 - x1
c = intercept
y = 2x - 7
y = -x + 1
y = 2x - 10
Step-by-step explanation:
Using y = mx+c
A. m=2 y=-7 x=0
-7= 2*0 + c
-7=c
y = 2*x - 7
y = 2x - 7
B. x1=3 x2=-2 y1=-4 y2=1
m = y2 - y1/ x2 - x1
m = 1+4 / -2-3
m = 5/-5 which is equal to -1
using any value for y and x, let's use x1 and y1
-2 = -1*3 + c
-2 = -3 + c
1 = c
y = -1*x + 1
y = -x + 1
C. x1=6 x2= 5 y1= 2 y2=0
m = y2 - y1/ x2 - x1
m = 0-2 / 5-6
m = -2/-1 which is equal to 2
using any value for y and x, let's use x1and y1
2 = 2*6 + c
2 = 12 + c
-10 = c
y = 2*x -10
y = 2x - 10
Find the 66th term of the arithmetic sequence
-13, -11, -9,...
Answer:
66th term =117
Step-by-step explanation:
Write an equation in point-slope form of the line that passes through the given point and with the given slope. (4,0);m=-1
Answer:
y - 0 = -1(x - 4)
Step-by-step explanation:
Point-slope form is this: y - y1 = m(x - x1)
We are given the values of m, x1, and y1, So all we have to do is input those values into the equation:
m = -1
(x1, y1) = (4, 0)
y - 0 = -1(x - 4)
I hope this helps. :)
I need help with this.
Answer:
x=7
Step-by-step explanation:
Factor the polynomial expression 8x^3-1
Answer:
Step-by-step explanation:
Solve the expression: 45x+-3(4-6)
Answer:
3(15x+2)
Step-by-step explanation:
A parallelogram has a base of 9 units and an area of 12 square units. What is the corresponding height for that base?
Answer:
12x9
Step-by-step explanation:
12x9 equals ____ square units
What is the correct word form of 12.607?
twelve and sixty-seven hundredths
twelve and six hundred seven thousandths
twelve and sixty-seven thousandths
twelve and six hundred seven hundredths
Twelve and six hundred seven thousandths
Does anyone know the answer
Answer:
630-420=210
Step-by-step explanation:
630 is miles to go and 420 is miles travel
.°. 630-420=210
help me if u knowwwwwwwww
Answer:
3(times)2x^8y^4+1
Step-by-step explanation:
How much larger is 6.3 x 10^6 than 4.9 x 10^4 ?
Answer: 625100
Step-by-step explanation:
To begin, we would start multiply both numbers one by one.
(6.3 x 10^6) - 4.9 x 10^4
6.3 x 10^6 = 6300000
4.9 x 10^4 = 49000
Now, subtract (6.3 x 10^6) and (4.9 x 10^4)
6300000. 49000
6300000 - 49000 = 6251000
Expand & simplify 4 ( g + 3 ) − 4 ( g + 6 )
Answer:
-12
Step-by-step explanation:
Can you plz answer 28
Answer:
265
Step-by-step explanation:
Find the slope of the line in the simplest form.
m= -4/6
m= 3/2
m= 2/3
m= 4/6
ANSWER ASAP
HELP HELP HELP HELP * i'll give brainliest*
What is the solution to the system of equation? Write you answer as a coordinate point.
Answer:
Step-by-step explanation:
Ok, so we have the equations:
7x-2y=-13
and
2y-5x=11
So first things first, we can cancel out 2y from both equations because they are common factors.
So we are left with the equations:
7x=-13
and
5x=11
So we add the two common factors and get:
12x=-24
And now we divide on both sides and get:
x=-2